Electrode tab, battery and preparation method thereof, and electric device
Patent Information
- Application Number
- CN202611433434.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-15
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]本申请所要解决的技术问题是提供一种电极极片、电池及其制备方法、用电设备,以解决相关技术中高压实密度的电极极片因内部孔隙率低而导致的浸润不良的问题
本申请实施例提供一种电极极片、电池及其制备方法、用电设备,该电极极片包括集流体和设置于集流体表面的活性物质层,活性物质层包括压敏型微球,压敏型微球包括内核和外壳,外壳设置于内核表面,内核包括添加剂,添加剂可溶于电解液,外壳包括脆性材料,外壳具有微裂纹。在本申请中,活性物质层中分散有压敏型微球,该压敏型微球的外壳为脆性材料,能够将内核添加剂与外界物理隔离,避免内核在浆料搅拌工序、涂布工序和干燥工序提前溶解或失效;在电极极片辊压工序,在机械应力下压敏型微球的外壳产生微裂纹,并且仍作为硬性支撑点存在于活性物质层内部,抵抗机械应力对电极极片内部孔隙的过度压缩,防止高压实密度下孔隙完全消失;在注液工序,电解液通过外壳的微裂纹渗入微球内部并溶解添加剂,形成外壳带有微裂纹且中空的微孔结构,该微孔结构与活性物质层的孔隙相互贯通,形成从极片表面到内部的连续导液通道,电解液通过该导液通道可均匀渗透至电极极片深处,提高浸润性,实现高保液量,进而提高高能量密度电池的安全性。
Smart Images

Figure CN122991985A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, and in particular to an electrode sheet, a battery and its preparation method, and an electrical device. Background Technology
[0002] Secondary batteries are widely used in electronic products, electric vehicles and energy storage due to their high energy density and long cycle life.
[0003] To meet the ever-increasing demand for extended driving range, improving the volumetric energy density of rechargeable batteries has become a continuous goal pursued by the industry, and increasing the compaction density of electrode sheets is one of the most direct and effective technical means at present.
[0004] However, high energy density inevitably leads to a sharp decrease in the porosity inside the electrode sheet, compressing the electrolyte wetting channels and making it extremely difficult for the electrolyte to penetrate deep into the electrode sheet. This results in "dry areas" inside the electrode sheet where the electrolyte is completely unwetted. During subsequent formation and capacity testing, these "dry areas" cannot participate in the electrochemical reaction normally, forcing the current to concentrate in the already wetted areas, causing localized polarization and overcharging, thus affecting the safety of high-energy-density batteries. Summary of the Invention
[0005] The technical problem to be solved by this application is to provide an electrode sheet, a battery and its preparation method, and an electrical device, so as to solve the problem of poor wetting caused by low internal porosity of high-density electrode sheets in related technologies.
[0006] To solve the above problems, this application provides the following technical solution: This application discloses an electrode sheet, characterized in that it includes a current collector and an active material layer disposed on the surface of the current collector, the active material layer including pressure-sensitive microspheres, the pressure-sensitive microspheres comprising: The core includes an additive that is soluble in an electrolyte; The outer shell is disposed on the surface of the core, the outer shell comprises a brittle material, and the outer shell has microcracks.
[0007] In some embodiments, the additive is used to form a solid electrolyte interface film.
[0008] In some embodiments, the active material layer has three-dimensional through channels, and the pores, microcracks and cavities of the active material layer are connected to form the three-dimensional through channels. The cavities are the accommodating spaces formed after the additives in the core dissolve in the electrolyte.
[0009] In some embodiments, the width of the microcrack is greater than or equal to 0.1 μm and less than 1 μm.
[0010] In some embodiments, the additive includes at least one of boron-containing lithium salts, cyclic carbonates, organic sulfates, and sulfonyl lactones.
[0011] In some embodiments, the electrode sheet satisfies at least one of the following conditions: A. The boron-containing lithium salt includes at least one of lithium bis(oxalato)borate and lithium difluorooxalato)borate; B. The cyclic carbonate includes at least one of vinylene carbonate and fluoroethylene carbonate; C. The organic sulfate ester includes at least one of vinyl sulfate and vinyl sulfite; D. The sulfonyl lactone includes at least one of 1,3-propanesulfonyl lactone and methylene disulfonate.
[0012] In some embodiments, the brittle material includes at least one of alumina, silicon dioxide, titanium dioxide, or lithium aluminate.
[0013] In some embodiments, the thickness of the outer shell is 10 nm to 100 nm, and / or, The particle size of the pressure-sensitive microspheres is 1 μm to 10 μm.
[0014] In some embodiments, the active material layer further includes an active material, wherein the mass percentage of the pressure-sensitive microspheres is 0.5% to 3% based on the total mass of the active material and the pressure-sensitive microspheres.
[0015] In some embodiments, the electrode sheet includes a positive electrode sheet, the compaction density of which is 2.5 g / cm³. 3 ~2.7 g / cm 3 ; and / or, the electrode sheet includes a negative electrode sheet, the compaction density of which is 1.5 g / cm³. 3 ~1.7 g / cm 3 .
[0016] This application also provides a battery including the electrode plates described above.
[0017] This application also provides a method for preparing a battery, comprising: Obtaining a slurry, wherein the slurry comprises pressure-sensitive microspheres, the pressure-sensitive microspheres comprising a core and a shell, the core comprising an additive soluble in an electrolyte, the shell disposed on the surface of the core, and the shell comprising a brittle material; The slurry is placed on the surface of the current collector and then subjected to drying and pressure treatment in sequence to obtain the electrode sheet. The pressure treatment causes microcracks to be generated in the outer shell. The electrode plates and the separator are stacked together and then encapsulated in the battery casing; An electrolyte is injected into the battery casing, and the electrolyte enters the interior of the pressure-sensitive microspheres through the microcracks, dissolving the additives to form a microporous structure inside the electrode plates.
[0018] This application embodiment also provides an electrical device, including the battery described above, wherein the battery serves as the power supply for the electrical device.
[0019] Compared with related technologies, the embodiments of this application have the following advantages: This application provides an electrode sheet, a battery, a method for preparing the same, and an electrical device. The electrode sheet includes a current collector and an active material layer disposed on the surface of the current collector. The active material layer includes pressure-sensitive microspheres, each of which includes a core and a shell. The shell is disposed on the surface of the core, and the core includes an additive that is soluble in an electrolyte. The shell includes a brittle material and has microcracks. In this application, pressure-sensitive microspheres are dispersed in the active material layer. The outer shell of the pressure-sensitive microspheres is made of a brittle material, which can physically isolate the core additives from the outside environment, preventing the core from dissolving or failing prematurely during the slurry stirring, coating, and drying processes. During the electrode rolling process, microcracks are generated in the outer shell of the pressure-sensitive microspheres under mechanical stress, but they still exist as rigid support points inside the active material layer, resisting excessive compression of the pores inside the electrode by mechanical stress and preventing the pores from completely disappearing under high compaction density. During the electrolyte injection process, the electrolyte penetrates into the microspheres through the microcracks in the outer shell and dissolves the additives, forming a microporous structure with microcracks and a hollow outer shell. This microporous structure is interconnected with the pores of the active material layer, forming a continuous liquid guiding channel from the surface of the electrode to the interior. The electrolyte can uniformly penetrate into the depth of the electrode through this liquid guiding channel, improving wettability, achieving high liquid retention, and thus improving the safety of high energy density batteries. Attached Figure Description
[0020] Figure 1 This is a schematic diagram of the preparation process of the electrode sheet provided in the embodiments of this application. Detailed Implementation
[0021] To make the above-mentioned objectives, features and advantages of this application more apparent and understandable, the application will be further described in detail below with reference to specific embodiments.
[0022] Reference Figure 1 As shown, this application provides an electrode sheet comprising a current collector and an active material layer disposed on the surface of the current collector. The active material layer includes pressure-sensitive microspheres, each comprising a core and a shell, with the shell disposed on the surface of the core. The core includes additives soluble in an electrolyte, and the shell comprises a brittle material having microcracks.
[0023] Battery manufacturing sequentially includes slurry mixing, coating, drying, rolling, liquid injection, and formation processes. In this embodiment, the pressure-sensitive microspheres perform multiple functions in different battery manufacturing processes, specifically: In the slurry mixing process, pressure-sensitive microspheres are mixed with active materials, conductive agents, binders and solvents to form a uniform slurry. Since the outer shell is a brittle material and insoluble in solvents, the core additives are completely encapsulated by the outer shell and will not dissolve or chemically deteriorate in the slurry system in advance, thus ensuring the effective loading of additives in subsequent processes.
[0024] In the coating and drying process, the slurry is uniformly coated on the surface of the current collector and heated to dry and remove the solvent to form a coating layer. At this time, the outer shell still maintains structural integrity, and the core additive is stably sealed inside the pressure-sensitive microspheres. Meanwhile, the pressure-sensitive microspheres are uniformly distributed in the active material layer, reserving rigid support points for the subsequent rolling process.
[0025] In the rolling process, the coating layer is compacted under high pressure to achieve the target compaction density, forming an active material layer and obtaining the electrode sheet. During the application of pressure, the outer shell develops microcracks or localized breakage under mechanical stress, but the pressure-sensitive microsphere skeleton does not completely disintegrate and remains as a rigid support point within the active material layer. This resists excessive compression of the pores within the active material layer by the rolling pressure, preventing the pores from completely disappearing under high compaction density, which helps to facilitate efficient wetting of the electrolyte in the subsequent process.
[0026] It should be noted that microcracks refer to micron-sized cracks that penetrate the shell wall or micron-sized cracks caused by local breakage of the shell wall, which are formed on the shell of pressure-sensitive microspheres under the mechanical stress of rolling. These microcracks can be confirmed by observing the cross-section of the electrode sheet after rolling with a scanning electron microscope (SEM).
[0027] In some embodiments, the width of the microcrack is greater than or equal to 0.1 μm and less than 1 μm. Controlling the width of the microcrack within this range can ensure that the electrolyte can smoothly enter the core through the microcrack, which helps to improve the rate performance and cycle stability of the electrode sheet. It can also prevent the outer shell from breaking prematurely or excessively due to the crack being too wide, causing the additives to be lost in advance. At the same time, it can also prevent the excessive loss of the integrity of the outer shell structure from adversely affecting the overall mechanical strength of the electrode sheet.
[0028] In some embodiments, the width of the microcrack is any one of 0.1 μm, 0.2 μm, 0.5 μm, 0.7 μm, 0.8 μm, and 0.9 μm, or the midpoint between two adjacent values.
[0029] In the cell assembly and electrolyte injection process, the rolled electrode sheets are wound or stacked to form the cell. After the electrolyte is injected, it quickly penetrates into the core of the pressure-sensitive microspheres through the microcracks in the outer shell. The additives in the core are dissolved upon contact with the electrolyte, forming a cavity. These cavities, microcracks, and pores in the active material layer are interconnected, which helps to form a three-dimensional through-channel. This three-dimensional through-channel constitutes a continuous liquid-conducting channel extending from the surface of the electrode sheet to its interior. The flow rate of electrolyte wetting into the electrode sheet through this three-dimensional through-channel increases per unit time, thereby shortening the injection and settling time, improving the wetting efficiency and uniformity of the electrolyte into the electrode sheet, and ensuring that active ions can be quickly and uniformly embedded and extracted on the surface of the active material particles during charging and discharging. This avoids the decrease in the utilization rate of active materials and local overcharging caused by insufficient local electrolyte, thus fully utilizing the capacity of the active material and improving cycle performance.
[0030] In summary, pressure-sensitive microspheres are dispersed within the active material layer. The outer shell of these microspheres is made of a brittle material, which physically isolates the core additives from the external environment, preventing premature dissolution or failure of the core during slurry mixing, coating, and drying processes. During the electrode rolling process, microcracks are generated in the outer shell of the pressure-sensitive microspheres under mechanical stress, yet they still exist as rigid support points within the active material layer, resisting excessive compression of the pores within the active material layer by mechanical stress and preventing the pores from completely disappearing under high compaction density. During the electrolyte injection process, the electrolyte penetrates into the pressure-sensitive microspheres through the microcracks in the outer shell and dissolves the additives, creating cavities, pores in the active material layer, and interconnections between the microcracks. This forms a three-dimensional through-hole channel from the surface of the electrode to its interior. The electrolyte can uniformly penetrate deep into the electrode through this three-dimensional through-hole channel, improving wettability, achieving high electrolyte retention, and thus improving the safety of high-energy-density batteries.
[0031] In some embodiments, the additive is a film-forming additive used to form a solid electrolyte interphase (SEI) film. During the formation process, the reduction potential of the film-forming additive is higher than that of the electrolyte solvent, and it can preferentially undergo reduction and decomposition on the electrode surface in the early stage of formation to form a solid electrolyte interphase film. The film structure is dense, uniform and stable, which can suppress direct contact between the electrolyte and the electrode, reduce the occurrence of side reactions, and the film is not easily remodeled and thickened during long-term cycling, and the interfacial impedance is stable, thereby ensuring the cycle stability and safety of the battery.
[0032] In contrast, without the participation of film-forming additives, solvent molecules undergo reduction and decomposition on the electrode surface during formation. This reduction has a low potential, occurs later in the process, and the resulting solid electrolyte interface film is primarily composed of low-molecular-weight organic lithium salts and carbonates. This porous structure has limited barrier properties against the electrolyte, making it difficult to effectively suppress ongoing side reactions between the electrolyte and electrode during subsequent cycles. Consequently, the solid electrolyte interface film thickens continuously during cycling, leading to a sustained increase in impedance and accelerated capacity decay. Therefore, this application utilizes the directional release of film-forming additives from the core of pressure-sensitive microspheres to form a high-quality solid electrolyte interface film during the formation stage. Furthermore, it eliminates the need for pre-addition of film-forming additives to the electrolyte, simplifying the electrolyte formulation and avoiding the negative impact of excessive film-forming additives on battery energy density and rate performance.
[0033] In some embodiments, the additive includes at least one of boron-containing lithium salts, cyclic carbonates, organic sulfates, and sulfonyl lactones.
[0034] Among them, at least one of boron-containing lithium salts, such as lithium bis(oxalato)borate and lithium difluorooxalato)borate, can preferentially reduce and decompose on the electrode surface to form a dense SEI film rich in B and F elements. This film has high ionic conductivity and good electronic insulation. At the same time, the F element in lithium difluorooxalato)borate can further enhance the hydrophobicity and chemical stability of the SEI film.
[0035] Cyclic carbonates, such as at least one of vinylene carbonate and fluoroethylene carbonate, can undergo ring-opening polymerization at a reduction potential to form a polycarbonate-based SEI film. This film is flexible, tightly bonded to the electrode surface, and can inhibit direct contact between the electrolyte and the electrode.
[0036] Organic sulfates include at least one of vinyl sulfate and vinyl sulfite. Vinyl sulfate has a higher reduction potential than vinyl carbonate, and can preferentially form a thinner, more compact and uniform SEI film on the graphite anode surface during the first charge and discharge process, thereby reducing interfacial impedance, improving the stability of the graphite anode, improving the battery's high-temperature cycling, high-temperature storage and low-temperature discharge performance, and reducing battery expansion after high-temperature storage. Vinyl sulfite also has high reduction activity and can preferentially reduce to form a stable SEI film on the graphite surface in propylene carbonate-based electrolytes. Sulfonolactones, such as at least one of 1,3-propanesulfonolactone and methylene disulfonate, can be reduced on the electrode surface to form an SEI film containing sulfonic acid groups, which has high thermal stability and antioxidant properties.
[0037] The above-mentioned additives form a dense solid electrolyte interface film in situ on the electrode surface, eliminating the need to add additional additives to the electrolyte, simplifying the electrolyte formulation, and reducing irreversible capacity loss.
[0038] In some embodiments, the brittle material includes at least one of alumina, silicon dioxide, titanium dioxide, or lithium aluminate.
[0039] Among them, alumina has high hardness, good electrochemical inertness and thermal stability. It can generate controllable microcracks under mechanical pressure, and it does not undergo side reactions within the battery's operating voltage range. Its residue on the inner wall of the pores does not affect battery performance. Silica also has brittleness and electrochemical inertness, and it has good wettability with electrolyte, which is beneficial for electrolyte wetting of the inner wall of the pores. Titanium dioxide has certain electrochemical activity in lithium-ion batteries, but it remains stable within the normal voltage range and does not affect the battery's cycle performance. Lithium aluminate itself is a lithium-ion conductor. Its residue on the inner wall of the pores not only does not block the ion transport path, but also provides additional lithium-ion conduction channels, which is beneficial for improving the ion transport efficiency of the inner wall of the pores.
[0040] The aforementioned brittle materials are insoluble in the slurry solvent, maintaining structural integrity during coating and drying, and stably sealing the core additives. At the same time, the aforementioned materials all have a certain degree of brittleness, and can generate micro-cracks under rolling mechanical stress without completely shattering, achieving pressure-sensitive controllable cracking.
[0041] In some embodiments, the thickness of the outer shell is 10nm~100nm to ensure that the outer shell has sufficient mechanical strength during the slurry stirring, coating and drying processes, so as to completely cover the core and prevent the core additives from being exposed or dissolved in advance; at the same time, it ensures that the outer shell can generate microcracks or local ruptures under mechanical stress such as rolling, so that the electrolyte can smoothly penetrate into the pressure-sensitive microspheres to dissolve the core, so as to prevent the core release from being delayed or incomplete due to the outer shell being too thick.
[0042] In some embodiments, the thickness of the shell is any one of 10 nm, 20 nm, 40 nm, 50 nm, 55 nm, 60 nm, 70 nm, 80 nm, 90 nm, 95 nm and 100 nm or an intermediate value between two adjacent values.
[0043] In some embodiments, the particle size of the pressure-sensitive microspheres is 1 μm to 10 μm, which matches the particle size of the electrode active material (typically submicron to several micrometers), so that the pressure-sensitive microspheres can be uniformly dispersed in the active material layer, avoiding sedimentation or scratches during the coating process due to excessively large particle size, or failure to form effective liquid guiding channels due to excessively small particle size.
[0044] In some embodiments, the particle size of the pressure-sensitive microspheres is any one of 1 μm, 2 μm, 3 μm, 5 μm, 8 μm, 9 μm and 10 μm or an intermediate value between two adjacent values.
[0045] In some embodiments, the preparation method of pressure-sensitive microspheres includes the following steps: pulverizing or sieving additive powder to obtain a core material with an appropriate particle size; placing the core material in a fluidized bed reactor, where it is fluidized under the action of a fluidizing gas; depositing a shell material precursor onto the surface of the core material using chemical vapor deposition to form a dense shell. The shell thickness is controlled to 10 nm to 100 nm by controlling the number of deposition cycles. After deposition, the microspheres are cooled, sieved, and classified to obtain pressure-sensitive microspheres with a shell thickness of 10 nm to 100 nm and an overall particle size of 1 μm to 10 μm.
[0046] In some embodiments, the active material layer further includes an active material, a conductive agent, and a binder.
[0047] Active materials are the components in electrode sheets that participate in electrochemical reactions and store energy, determining the battery's capacity, voltage plateau, and energy density. Taking lithium-ion batteries as an example, the positive and negative active materials achieve the interconversion of chemical energy and electrical energy through the extraction and insertion of lithium ions. The positive active material can be selected from at least one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, and lithium manganese oxide, while the negative active material can be selected from at least one of artificial graphite, natural graphite, silicon-carbon composite materials, silicon-oxygen composite materials, and lithium titanate.
[0048] Conductive agents are used to establish an effective electronic conduction network between active material particles and reduce the internal resistance of the electrode. They can be selected from at least one of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes, and graphene.
[0049] The binder is used to firmly bond the active material, conductive agent and pressure-sensitive microspheres to the current collector surface, maintaining the structural integrity and mechanical strength of the electrode sheet, and can be selected from at least one of polyvinylidene fluoride, styrene-butadiene rubber, sodium carboxymethyl cellulose, polyacrylic acid and polytetrafluoroethylene.
[0050] In some embodiments, based on the total mass of the active material and the pressure-sensitive microspheres, the mass percentage of the pressure-sensitive microspheres is 0.5% to 3%. Within this range, the pressure-sensitive microspheres can form an appropriate amount of liquid-conducting channels inside the high-density electrode sheet without significantly reducing the active material loading, ensuring uniform electrolyte wetting and achieving a balance between electrolyte wettability and volumetric energy density. At the same time, they can also provide an appropriate amount of additives to help form an SEI film at the electrode sheet interface during the formation process, thereby improving the cycle life of the battery.
[0051] Compaction density is a crucial parameter in lithium-ion battery manufacturing. It refers to the mass of material contained within a unit volume of an electrode under a given pressure. During the manufacturing process, compaction density significantly impacts battery performance. Generally, it is closely related to electrode specific capacity, efficiency, internal resistance, and battery cycle performance.
[0052] In some embodiments, the electrode sheet includes a positive electrode sheet, which comprises a positive current collector and a positive active material layer disposed on the surface of the positive current collector. The positive active material layer comprises a positive active material, a conductive agent, a binder, and pressure-sensitive microspheres, etc. The compacted density of the positive electrode sheet is 2.5 g / cm³. 3 ~2.7 g / cm 3 Within this high compaction density range, sufficient electronic conductive contact is formed between the positive electrode active material particles, while an appropriate amount of porosity is retained inside the positive electrode sheet. During the rolling process, the pressure-sensitive microspheres develop microcracks in their outer shell but maintain the integrity of their spherical framework. After electrolyte injection, the core additives dissolve to form liquid-conducting channels, providing continuous pathways for electrolyte wetting. This improves the volumetric energy density of the battery while ensuring the dynamic performance and cycle stability of the positive electrode sheet. In some embodiments, the compaction density of the positive electrode sheet is 2.5 g / cm³. 3 2.6 g / cm 3 Or 2.7g / cm 3 .
[0053] In some embodiments, the electrode sheet includes a negative electrode sheet, which includes a negative current collector and a negative active material layer disposed on the surface of the negative current collector. The negative active material layer includes a negative active material, a conductive agent, a binder, and pressure-sensitive microspheres.
[0054] The compacted density of the negative electrode sheet is 1.5 g / cm³. 3 ~1.7 g / cm 3 Within this high compaction density range, the particles of the negative electrode active material maintain suitable conductive contact and structural integrity, while the electrode retains an appropriate amount of porosity. During the rolling process, the pressure-sensitive microspheres develop microcracks in their outer shell, forming liquid-conducting channels that provide continuous liquid channels for electrolyte wetting. This improves the volumetric energy density of the battery while ensuring the dynamic performance and cycle stability of the negative electrode. In some embodiments, the compaction density of the negative electrode is 1.5 g / cm³. 3 1.6 g / cm 3 Or 1.7g / cm 3 .
[0055] This application also provides a battery, including a positive electrode, a negative electrode, a separator disposed between the positive and negative electrode, and an electrolyte. The positive and negative electrode are electrode sheets from any of the foregoing embodiments. The battery is assembled into a cell by winding or stacking the positive electrode, separator, and negative electrode, and then packaged after injecting electrolyte.
[0056] Electrolyte plays a core role in the battery as an ion transport medium, conducting active ions between the positive and negative electrodes to achieve charge balance during charging and discharging.
[0057] Taking a lithium-ion battery as an example, the electrolyte includes a lithium salt and an organic solvent. The lithium salt provides lithium ions that can migrate back and forth between the positive and negative electrodes, including at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium hexafluoroaluminate, lithium tetrafluoroborate, lithium difluorooxalate borate, lithium dioxoyl borate, lithium difluorophosphate, and lithium nitrate. The organic solvent includes cyclic ester solvents and chain ester solvents. In some embodiments, the cyclic ester solvent includes at least one of ethylene carbonate, propylene carbonate, butenyl carbonate, fluoroethylene carbonate, and γ-butyrolactone; the chain ester solvent includes at least one of dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, and diphenyl carbonate. The organic solvent is used to dissolve the lithium salt and form a low-viscosity, high-dielectric-constant ion-conducting medium, allowing lithium ions to migrate rapidly therein.
[0058] During the electrolyte injection process, the electrolyte penetrates into the interior of the pressure-sensitive microspheres through the microcracks in their outer shell, dissolving and releasing the core additives. The microcracked outer shell and hollow core of the pressure-sensitive microspheres create in-situ liquid-conducting channels within the active material layer, allowing the electrolyte to rapidly and uniformly penetrate deep into the electrode sheet, improving wettability and achieving high electrolyte retention. Simultaneously, the dissolved additives diffuse with the electrolyte to the surface of the electrode sheet, participating in the formation of a dense SEI film during the formation process. Therefore, the synergistic effect of the electrolyte components and the pressure-sensitive microspheres simultaneously achieves the dual functions of in-situ pore creation and interface formation after electrolyte injection.
[0059] The separator is a porous thin film material located between the positive and negative electrodes in a lithium-ion battery. It serves as a physical barrier, preventing direct contact between the positive and negative electrodes that could lead to a short circuit. Simultaneously, it acts as an ion channel, allowing lithium ions to freely pass through its micropores during charging and discharging. Furthermore, the separator must possess good electrolyte wettability to ensure that the electrolyte fully fills the pores, forming a continuous ion conduction channel.
[0060] In some embodiments, this application also provides an electrical device including a battery, which serves as a power supply for the device. It should be noted that the battery disclosed in this embodiment has the same structure as the battery in the above embodiments, and its beneficial effects are similar. Therefore, it will not be repeated here; relevant details can be found in the description of the battery embodiments.
[0061] In some embodiments, the electrical device may further include an energy storage cabinet, a mobile phone, a tablet, a laptop, an electric toy, a ship, a spacecraft, etc. The electric toy may include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc., while the spacecraft may include airplanes, rockets, space shuttles, and spacecraft, etc.
[0062] To make the inventive objectives, technical solutions, and beneficial effects of this application clearer, the present application is further described below with reference to embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of this application.
[0063] Example 1 (1) Preparation of positive electrode sheet Pressure-sensitive microspheres were prepared with a core of lithium bis(oxalateborate)borate (LiBOB) crystals and an outer shell of alumina with a thickness of 50 nm. The overall particle size of the pressure-sensitive microspheres was 3 μm.
[0064] Using lithium iron phosphate as the positive electrode active material, lithium iron phosphate and pressure-sensitive microspheres were mixed at a mass ratio of 98.5:1.5 to obtain a composite powder. The composite powder, conductive carbon black, polyvinylidene fluoride (PVDF) binder, and dispersant were then mixed at a mass ratio of 95.2:1:3.5:0.3 and added to N-methylpyrrolidone, stirred until homogeneous, to obtain a positive electrode slurry. Using aluminum foil as the positive electrode current collector, the positive electrode slurry was coated onto the aluminum foil surface, dried, and cold-pressed to a compaction density of 2.5 g / cm³. 3 Then, through cutting and slitting, positive electrode sheets are obtained.
[0065] (2) Preparation of negative electrode sheet Artificial graphite, conductive carbon black, sodium carboxymethyl cellulose, and styrene-butadiene rubber were mixed in a mass ratio of 96:0.5:1.5:2, and then added to deionized water and stirred until homogeneous to obtain the negative electrode slurry. Using copper foil as the negative electrode current collector, the negative electrode slurry was coated onto the surface of the copper foil, dried, and cold-pressed until a compaction density of 1.5 g / cm³ was achieved. 3 Then, through cutting and slitting, negative electrode sheets are obtained.
[0066] (3) Assemble bare cells The positive electrode, separator, negative electrode, and separator are stacked in sequence, with the separator positioned between the positive and negative electrodes to provide isolation. Then, they are wound into a battery cell, and tape is applied to the winding point to obtain a bare battery cell.
[0067] (4) Preparation of electrolyte Under an argon protective atmosphere, ethylene carbonate and methyl ethyl carbonate were mixed at a volume ratio of 3:7, and lithium hexafluorophosphate was added to make the concentration of lithium hexafluorophosphate 1.0 mol / L. The mixture was stirred until homogeneous to obtain the electrolyte.
[0068] (5) Assemble lithium-ion batteries The bare cells are assembled into aluminum-cased cells, vacuum dried at 100°C, and then injected with electrolyte. After processes such as settling, formation, and capacity testing, a lithium-ion battery is obtained.
[0069] Example 2 The difference between Example 2 and Example 1 is that the core of the pressure-sensitive microsphere is vinylene carbonate (VC) crystals, the outer shell is silicon dioxide, the thickness of the outer shell is 10 nm, and the overall particle size of the pressure-sensitive microsphere is 1 μm.
[0070] Example 3 The difference between Example 3 and Example 1 is that the core of the pressure-sensitive microsphere is 1,3-propanesulfonate (PS) crystals, the outer shell is lithium aluminate, the thickness of the outer shell is 100 nm, and the overall particle size of the pressure-sensitive microsphere is 10 μm.
[0071] Example 4 The difference between Example 4 and Example 1 is that the mass ratio of lithium iron phosphate to pressure-sensitive microspheres in step (1) is 99.5:0.5.
[0072] Example 5 The difference between Example 5 and Example 1 is that the mass ratio of lithium iron phosphate to pressure-sensitive microspheres in step (1) is 97:3.
[0073] Example 6 The difference between Example 6 and Example 1 is that the compaction density of the positive electrode sheet in step (1) is 2.7 g / cm³. 3 In step (2), the compaction density of the negative electrode sheet is 1.7 g / cm³. 3 .
[0074] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that pressure-sensitive microspheres were removed in step (1), and lithium iron phosphate, conductive carbon black, binder polyvinylidene fluoride and dispersant were mixed in a mass ratio of 95.2:1:3.5:0.3.
[0075] The relevant parameters for preparing lithium-ion batteries in each embodiment and comparative example are shown in Table 1.
[0076] Table 1
[0077] Test Example 1 The cross-section of the rolled electrode sheet was observed using a scanning electron microscope to confirm the existence and width of the microcracks. During the test, scanning electron microscope images were acquired from at least three different fields of view on the cross-section of the electrode sheet. The width of at least ten microcracks randomly selected from each image was measured, and the arithmetic mean of all measurements was calculated as the average width of the microcracks.
[0078] Test Example 2 Wetting effect test: After electrolyte injection, the lithium-ion battery was connected to a voltage acquisition device. Voltage signals between the positive and negative electrodes of the cell were continuously acquired during the 0-24 hour settling period, and the voltage-time curve was recorded. The voltage-time curve was differentiated to obtain the dV / dt curve. This dV / dt curve characterizes the rate of voltage change during the settling process. When the electrolyte has not fully wetted the electrode, the local concentration and potential differences within the cell are large, resulting in a rapid voltage change rate, and the dV / dt curve exhibits large fluctuations and a high absolute value. As the electrolyte gradually penetrates deeper into the electrode, the concentration polarization within the cell gradually disappears, the potential stabilizes, and the voltage change rate gradually decreases until it approaches zero. The time point when the absolute value of dV / dt is less than 0.01 mV / min for one consecutive hour is defined as the wetting equilibrium time. The average value of three parallel samples was taken for each example and comparative example.
[0079] Test Example 3 Cyclic performance test: At a temperature of 25 ℃, constant current charge and discharge was performed at 0.33C within a voltage range of 2.5V~3.65V. The initial charge and discharge specific capacity at 0.33C was measured. The discharge capacity was measured as C1 after one cycle of constant current charge and discharge at 0.33C, and the discharge capacity was measured as C2 after 200 cycles of constant current charge and discharge at 0.33C. The capacity retention rate after 200 cycles at 0.33C was calculated as C2 / C1×100%. This capacity retention rate can characterize the battery's capacity retention capability after 200 cycles. The higher the value, the less capacity decay and the better the cycle stability of the battery during long-term use.
[0080] The performance of the lithium-ion batteries prepared in the above embodiments and comparative examples was tested, and the test results are shown in Table 2.
[0081] Table 2
[0082] As can be seen from Table 2, by adding pressure-sensitive microspheres in each embodiment, the microcracks generated on the shell of the pressure-sensitive microspheres during rolling, the pores of the active material layer, and the cavities left after the additives are dissolved are interconnected to form a three-dimensional through-hole, which shortens the immersion equilibrium time.
[0083] Furthermore, the core materials (LiBOB, VC, PS) in Examples 1-3 effectively participated in the formation of the SEI film during the formation stage, and the shell materials (alumina, silicon dioxide, lithium aluminate) could generate microcracks during rolling and release the core after liquid injection. All three combinations achieved a reduction in wetting equilibrium time and an improvement in capacity retention. Among them, the combination of LiBOB and alumina had the shortest wetting equilibrium time (10h), indicating that the electrolyte wetting efficiency and film formation effect of this combination were relatively better.
[0084] As can be seen from Examples 1, 4, and 5, as the proportion of pressure-sensitive microspheres increases from 0.5% to 3%, the wetting equilibrium time tends to shorten and the capacity retention rate tends to increase. However, when the proportion of pressure-sensitive microspheres is too high (3%, Example 5), the increase slows down, indicating that an addition of 1.5% can achieve a good channel connectivity effect. The marginal benefit of further increasing the amount of pressure-sensitive microspheres for performance improvement is diminishing.
[0085] Compared to Example 1, the compaction density of Example 6 was increased (positive electrode 2.7 g / cm³). 3 Negative electrode 1.7 g / cm 3 Even with low wetting equilibrium time and high capacity retention, the pore-forming effect of pressure-sensitive microspheres is still maintained, proving that the pore-forming effect of pressure-sensitive microspheres is more significant under high compaction density.
[0086] Comparative Example 1, without the addition of pressure-sensitive microspheres, had a longer immersion equilibrium time (16 h). This is because under high solid density, the pores inside the electrode are excessively compressed, resulting in an unconnected pore structure and making it difficult for the electrolyte to penetrate deep into the electrode. At the same time, due to the lack of directional release of additives inside the electrode, the SEI film is formed solely by the reduction and decomposition of trace impurities or solvents that may remain in the electrolyte during the formation process. This SEI film has a loose and uneven structure, and cannot effectively suppress the side reactions between the electrolyte and the electrode surface during long-term cycling, resulting in rapid capacity decay and low capacity retention.
[0087] Although preferred embodiments of the present application have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of the embodiments of the present application.
[0088] The present application provides a detailed description of an electrode sheet, a battery, its preparation method, and an electrical device. Specific examples have been used to illustrate the principles and implementation methods of the present application. The descriptions of the above embodiments are only for the purpose of helping to understand the methods and core ideas of the present application. At the same time, those skilled in the art will recognize that there will be changes in the specific implementation methods and application scope based on the ideas of the present application. Therefore, the content of this specification should not be construed as a limitation of the present application.
Claims
1. An electrode sheet, characterized in that, The system includes a current collector and an active material layer disposed on the surface of the current collector. The active material layer includes pressure-sensitive microspheres, which comprise: The core includes an additive that is soluble in an electrolyte; The outer shell is disposed on the surface of the core, the outer shell comprises a brittle material, and the outer shell has microcracks.
2. The electrode sheet according to claim 1, characterized in that, The additive is used to form a solid electrolyte interface film.
3. The electrode sheet according to claim 1 or 2, characterized in that, The active material layer has three-dimensional through channels. The pores, microcracks and cavities of the active material layer are connected to form the three-dimensional through channels. The cavities are the accommodating spaces formed after the additives in the core dissolve in the electrolyte.
4. The electrode sheet according to any one of claims 1 to 3, characterized in that, The width of the microcrack is greater than or equal to 0.1 μm and less than 1 μm.
5. The electrode sheet according to any one of claims 1 to 4, characterized in that, The additives include at least one of boron-containing lithium salts, cyclic carbonates, organic sulfates, and sulfonyl lactones.
6. The electrode sheet according to claim 5, characterized in that, At least one of the following conditions must be met: A. The boron-containing lithium salt includes at least one of lithium bis(oxalato)borate and lithium difluorooxalato)borate; B. The cyclic carbonate includes at least one of vinylene carbonate and fluoroethylene carbonate; C. The organic sulfate ester includes at least one of vinyl sulfate and vinyl sulfite; D. The sulfonyl lactone includes at least one of 1,3-propanesulfonyl lactone and methylene disulfonate.
7. The electrode sheet according to any one of claims 1 to 6, characterized in that, The brittle material includes at least one of alumina, silicon dioxide, titanium dioxide, or lithium aluminate.
8. The electrode sheet according to any one of claims 1 to 7, characterized in that, The thickness of the outer shell is 10 nm to 100 nm, and / or, The particle size of the pressure-sensitive microspheres is 1 μm to 10 μm.
9. The electrode sheet according to any one of claims 1 to 8, characterized in that, The active material layer also includes active materials, and the mass percentage of the pressure-sensitive microspheres is 0.5% to 3% based on the total mass of the active materials and the pressure-sensitive microspheres.
10. The electrode sheet according to any one of claims 1 to 9, characterized in that, The electrode sheet includes a positive electrode sheet, and the compaction density of the positive electrode sheet is 2.5 g / cm³. 3 ~2.7 g / cm 3 ; And / or, the electrode sheet includes a negative electrode sheet, the compaction density of which is 1.5 g / cm³. 3 ~1.7 g / cm 3 .
11. A battery, characterized in that, Includes the electrode sheet as described in any one of claims 1 to 10.
12. A method for preparing a battery, characterized in that, include: Obtaining a slurry, wherein the slurry comprises pressure-sensitive microspheres, the pressure-sensitive microspheres comprising a core and a shell, the core comprising an additive soluble in an electrolyte, the shell disposed on the surface of the core, and the shell comprising a brittle material; The slurry is placed on the surface of the current collector and then subjected to drying and pressure treatment in sequence to obtain the electrode sheet. The pressure treatment causes microcracks to be generated in the outer shell. The electrode plates and the separator are stacked together and then encapsulated in the battery casing; An electrolyte is injected into the battery casing, and the electrolyte enters the interior of the pressure-sensitive microspheres through the microcracks, dissolving the additives to form a microporous structure inside the electrode plates.
13. An electrical appliance, characterized in that, Includes the battery as described in claim 11, wherein the battery serves as the power supply for the electrical device.